If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + -3 + 5x = 22 Reorder the terms: -3 + 20x + 5x = 22 Combine like terms: 20x + 5x = 25x -3 + 25x = 22 Solving -3 + 25x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 25x = 22 + 3 Combine like terms: -3 + 3 = 0 0 + 25x = 22 + 3 25x = 22 + 3 Combine like terms: 22 + 3 = 25 25x = 25 Divide each side by '25'. x = 1 Simplifying x = 1
| 7y-5=9y+25 | | 0.12(y-6)+0.18y=0.04y-0.05(30) | | k-12=34 | | 4x^2+39x+56=0 | | -14=7(s-7) | | 15=(3h-1) | | 2-7[9-(6y-6)]= | | -4.65+0.19x=23.85 | | 7.4p-9.2p=-2.6+5.3 | | 5x^2-9x-80=0 | | -4+5x=-4x-4 | | Y-12=24 | | 7=4(5-2x)+3y | | 3(h-4)=-.5(24-6h) | | 7(3x-2)+18x+7=12x+7 | | (4n+17)+(n-2)=180 | | 9+t=14 | | (x+4)(x+4)+6=87 | | x+2=2x+15 | | 20+(-26)+34-(-37)-62= | | 10x^2+15x-8x-12=0 | | 3(x-3)+4(x)=9 | | 3*b-4=5v-2 | | (12x^2)-4x-5=0 | | 2(w-8)=4 | | 11.2j+11.55=j+10.1j+10.35 | | 13x+13=5x+11 | | x(x-20)=-20(2x+5) | | (2a+5)(a-6)= | | (15x^2+70x+25)=0 | | 2*s+3*s-1=18 | | 2(x+5)=3(x-(2-x)) |